2012
DOI: 10.1016/j.jprot.2012.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Observing the invisible through imaging mass spectrometry, a window into the metabolic exchange patterns of microbes

Abstract: Many microbes can be cultured as single-species communities. Often, these colonies are controlled and maintained via the secretion of metabolites. Such metabolites have been an invaluable resource for the discovery of therapeutics (e.g. penicillin, taxol, rapamycin, epothilone). In this article, written for a special issue on imaging mass spectrometry, we show that MALDI-imaging mass spectrometry can be adapted to observe, in a spatial manner, the metabolic exchange patterns of a diverse array of microbes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 34 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…The invaluable tool of MS has played a major role in characterizing biosynthetic release factors for a diverse number of organisms (19). Over the past decade, the field has spawned several innovative methods to optimize data collection, processing, and organization.…”
mentioning
confidence: 99%
“…The invaluable tool of MS has played a major role in characterizing biosynthetic release factors for a diverse number of organisms (19). Over the past decade, the field has spawned several innovative methods to optimize data collection, processing, and organization.…”
mentioning
confidence: 99%
“…Note also that the ions of m/z 619.1 (Figure 10b), 1643.6 (Figure 10f) and 1971.5 (Figure 10g) are in greater abundance between colonies and, therefore, related to "cross talking". 14,15,22 The ion of m/z 638.5 (Figure 10c) is, however, in greater abundance only on the colonies of the N. harveyana PCC 7804. The ion of m/z 989.4 (Figure 10d) is detected in all the three colonies, whereas that of m/z 1276.3 (Figure 10e) is abundant except for the colonies of the M. aeruginosa PCC 7820.…”
Section: Resultsmentioning
confidence: 99%
“…MALDI-IMS combines the high sensitivity and selectivity of MS with 2D surface screening analysis, and its scope has been expanded to deliver spatial distributions of several biomolecules such as metabolites and lipids in different biological matrices. 13 This technique has also been applied for analysis of microbial natural products, 14 microbial interactions 15 and metabolic profiling of microorganisms. 16 Recently, MALDI-IMS has been tested for filamentous marine cyanobacteria, 17 showing the spatial distribution of natural products.…”
Section: Maldi Imaging Mass Spectrometry Of Fresh Water Cyanobacteriamentioning
confidence: 99%
“…It was shown that many of the imaged alkaloids form specific tissue associations within the complexity of the sponge matrix. A study on metabolic exchange patterns of microbes revealed the complexity of molecular communication of microbes including the secretion of parmaceutically interesting compounds such as antibiotics or cancer therapeutical drugs 222,223 . A number of other studies were reported in this context recently 15,[224][225][226][227] .…”
Section: Microorganisms Fungi and Spongesmentioning
confidence: 99%